Anxiety reactions in prisoners : The role of personality, stress, and coping processes - Buško, Vesna (Array, 1997)
Within a framework of transactional stress and coping theory, the study examines the role of individual, situational and mediating cognitive factors in accounting for anxiety in prison inmates. Relevant demographic and criminological measures, and self-report instruments for the assessment of personality, some situational features, and mediating processes - cognitive appraisals and coping strategies, were taken in the sample of 475 males incarcerated in Croatian penal institutions of minimum, medium or maximum security level. Endler self-report state anxiety scale (EMAS-S) was administered as a short-term measure of inmate adjustment to imprisonment. Hierarchical regression procedures were performed to assess relative predictive power of particular groups of individual, situational and mediating variables, with the cognitive appraisal on event controllability taken as a moderator variable. Personality dimensions and two sets of mediating processes variables significantly contributed to the criterion variance. Total amount of variance in anxiety scores explained by the whole system of employed predictors was 59% and 70%, for the low and high event controllability groups, respectively. Findings support theoretical views regarding mediating role of coping mechanisms and, to the lesser extent, the moderating role of perceived event controllability in establishing mutual relations among the components within the stress model.